2022
DOI: 10.1136/bmjpo-2022-001528
|View full text |Cite
|
Sign up to set email alerts
|

Are children with obesity at school entry more likely to have a diagnosis of a musculoskeletal condition? Findings from a systematic review

Abstract: BackgroundChildren with obesity at school entry are at increased risk of persistent obesity throughout childhood and adulthood. Little is known about associations with adverse health outcomes with onset during childhood including those affecting the musculoskeletal system. We examined the association between obesity present at school entry and adverse musculoskeletal diagnoses with onset during childhood.MethodsWe searched three electronic databases to identify longitudinal studies published in English between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This review predominantly summarised cross-sectional studies, leaving the temporal relationship between exposure and outcome difficult to ascertain. Our recent systematic review of longitudinal evidence found that children with obesity at school entry are more likely to experience back pain, SCFE or fractures during childhood, but there were few eligible studies included and they were of moderate quality 12. We noted that potential confounding variables were inconsistently accounted for in the included studies.…”
Section: Introductionmentioning
confidence: 98%
“…This review predominantly summarised cross-sectional studies, leaving the temporal relationship between exposure and outcome difficult to ascertain. Our recent systematic review of longitudinal evidence found that children with obesity at school entry are more likely to experience back pain, SCFE or fractures during childhood, but there were few eligible studies included and they were of moderate quality 12. We noted that potential confounding variables were inconsistently accounted for in the included studies.…”
Section: Introductionmentioning
confidence: 98%